2007
DOI: 10.1002/bip.20826
|View full text |Cite
|
Sign up to set email alerts
|

Review fluorescence correlation spectroscopy for probing the kinetics and mechanisms of DNA hairpin formation

Abstract: This article reviews the application of fluorescence correlation spectroscopy (FCS) and related techniques to the study of nucleic acid hairpin conformational fluctuations in free aqueous solutions. Complimentary results obtained using laser-induced temperature jump spectroscopy, single-molecule fluorescence spectroscopy, optical trapping, and biophysical theory are also discussed. The studies cited reveal that DNA and RNA hairpin folding occurs by way of a complicated reaction mechanism involving long- and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 102 publications
3
56
0
Order By: Relevance
“…[4,5] Although our hairpin data were consistent with a two-state model via the chi-squared metric, we also observed a systematic deviation between our data and the model. Recent studies of DNA hairpin dynamics have identified putative intermediates in the folding pathway, [36,37] which could explain this discrepancy. However, we caution that the detection of such intermediates by PDA should involve the use of novel experimental controls, and not simply an increase in the number of free parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] Although our hairpin data were consistent with a two-state model via the chi-squared metric, we also observed a systematic deviation between our data and the model. Recent studies of DNA hairpin dynamics have identified putative intermediates in the folding pathway, [36,37] which could explain this discrepancy. However, we caution that the detection of such intermediates by PDA should involve the use of novel experimental controls, and not simply an increase in the number of free parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to more complex kinetic schemes, as identified in recent biophysical studies of DNA hairpins. [36,37] While some of these behaviors are expected to occur on timescales too short to be detected by PDA (e.g. multiple loop orientations in the open conformation), longerlived states (e.g.…”
mentioning
confidence: 99%
“…19 This hypothesis has been challenged by several recent studies that suggest a more complex pathway, involving intermediate states containing misfolded or partially folded configurations. [20][21][22] Additionally, there have been diverse, and sometimes contradictory, experimental observations and interpretations of hairpin formation kinetics. Fluorescence energy transfer and fluorescence correlation spectroscopy measurements 23 have reported an Arrhenius temperature dependency with a positive activation enthalpy for the hairpin closing rates.…”
Section: Introductionmentioning
confidence: 99%
“…Data about the collective motion of DNA/RNA helical domains arising from structural fluctuations of the duplex (bending and twisting) are almost non-existent in the literature, especially for short duplexes. However, it can be inferred that these motions mainly cover the range from tens of nanosecond to tens of microseconds (Hogan et al 1982;Naimushin et al 2000;Orden and Jung 2008;Porschke 2007;Schwieters and Clore 2007;Shajani and Varani 2007), although motions in the range 20-400 ls have been reported (Kojima et al 2001). Together, these considerations indicate that in most cases, energy transfer captures a transient ''static'' configuration of the duplex, whereas the slow acquisition rate allows the DNA/RNA duplex and associated fluorophores to adopt all possible configurations within the experimental period used for data acquisition.…”
Section: Discussionmentioning
confidence: 99%